Cover SHEs: Conference Series SNBK 2019 and WTPP 2019 - Cover SHEs: Conference Series SNBK 2019 and WTPP 2019 (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Cover SHEs: Conference Series SNBK 2019 and WTPP 2019